PENGARUH KEBIASAAN BELAJAR DAN PERHATIAN ORANG TUA TERHADAP PRESTASI BELAJAR DI SMK BATIK 2 SURAKARTA - David Andriawan; Cicilia Dyah Sulistyaningrum Indrawati; Susantiningrum Susantiningrum (JIKAP (Jurnal Informasi dan Komunikasi Administrasi Perkantoran), 2022)
The purpose of this study is to determine whether there is an effect of: (1) study habits on learning achievement in the subject of financial administration, (2) parents 'attention to learning achievement (3) study habits and parents' attention to learning achievement. This research uses quantitative methods. The population was all 44 students of class XI AP SMK Batik 2 Surakarta. The data collection technique uses the documentation method and a questionnaire. Test the validity of the instrument usingcorrelation Product Moment, and reliability testing usingformula Cronbach's Alpha. The data analysis technique used is multiple regression analysis with SPSS 17. The prerequisite test uses the normality test, linearity test, and multicollinearity test. The results show there was a positive and significant influence between: (1) study habits on learning achievement tcount = 4.285> ttable 2.021, (2) parents' attention to learning achievement tcount = 2.193> ttable 2.021, (3) habits learning and parental attention to learning achievement Fcount = 243,388> Ftable = 3,928. With the effective contribution of learning habits (X1) of 44.90%, the effective contribution of parents' attention (X2) of 18.0% and the relative contribution of learning habits (X1) 77.15%, the relative contribution of parental attention (X2) 28, 53%.